The role of the reference source in improving the CIE colour-rendering index for visual perception optimisation - Leuschner, F.W. (Friedrich Wilhelm) (University of Pretoria, 2019)
Thesis (PhD (Electronic Engineering))--University of Pretoria, 2019.